Science Learning Achievement; Three Dimension-Media Innovation in Contextual Learning Approach - Widiana, I Wayan; Kusmariatni, Nyoman; Sedana, Dewa Nyoman; Riastini, Putu Nanci (LPPM Undiksha, 2019)
Science learning achievement is low in some elementry schools in Bali and it is suspected that learning process is one of the factors that has caused this. Hence, there is a need for innovations in learning to improve learning process which has so far taken place (conventional). This study wasa aimed at finnding out the difference in science learning achievement between students who are taught through contextual learning which uses three dimension media and those who are taught through conventional learning..this is a quasi-experimental research with non equivalent post-test only control group design. The population used in this study was the fourth grade students af elementary schools in Gugus 1 Singaraja with the total number of eight schools. The sample in this study was selected using random sampling. Out of the eight schools in Gugus 1 Singaraja, two schools wereselected, namely SD No. 5 Banyuning as experiment group and SD No.6 Banyuning as conrol group.. the data gathered inthis study was in the form of science learning achievement. The instrument used to collect the data was an objective test or multiple choice. The data were analyzed using inferential statistics or t-test. The result showed that science learning achievement in the group where three dimension media were used had the mean score of 20.75 , which is higher than the group where conventional learning was used , whose mean score was 17. 08. This result was confirmed by hypothesis testing in which it was obtained that tobs. > tc.v.. This means that the implementation of contextual learning approach which was aided with three dimenisionmedia had a positive effect on science learning achivement.